INNOVATIVE AND TECHNOLOGICAL FILLING OF MARKETING STRATEGIES FOR BUSINESS COMPETITIVENESS IN THE SERVICES SECTOR (Development Service Industry Management, 2025)
The article focuses on the features of business development in the services sector, a distinctive feature of which is a fairly high level of personalization in working with the target audience. It is noted that this requires qualified formation of a marketing strategy to implement the tasks of segmentation, market targeting and positioning of value propositions in the form of services on it. Their content and quality should meet the consumer's needs as fully as possible - this is a necessary condition for the competitiveness of business in the services sector. It is emphasized that for this, the marketing strategy should ensure the growth of the company's recognition (to increase its presence in the market) and increase the economic efficiency of the business - thanks to a method of positioning services relevant to target audiences and reasonable forms and methods of stimulating their implementation. With high variability of consumer needs, the marketing strategy should be based on technologies that will ensure the proactivity of the service producer in working with target groups of consumers. Such proactivity is achieved by using innovative digital technologies that can solve many different tasks associated with significant data sets. It is important to use them with maximum efficiency in each market context. The paper describes the most common innovative digital technologies used in the field of marketing, highlighting those that are effective for implementing strategic marketing tasks. It is noted that the use of certain technologies depends on the type of marketing strategy, which is formed in relation to the strategic goals of the business in the context of the chosen competitive strategy. Examples are given and the feasibility of such a choice for the hotel business is argued.
Keywords: cognitive component of the value proposition; value personalization; proactivity; hotel business; digital technologies; competitiveness